Why is it so difficult to represent stably stratified conditions in numerical weather prediction (NWP) models?. (2nd April 2013) - Sandu, Irina; Beljaars, Anton; Bechtold, Peter; Mauritsen, Thorsten; Balsamo, Gianpaolo
Abstract : [1] In the 1990s, scientists at European Centre for Medium‐Range Weather Forecasts (ECMWF) suggested that artificially enhancing turbulent diffusion in stable conditions improves the representation of two important aspects of weather forecasts, i.e., near‐surface temperatures and synoptic cyclones. Since then, this practice has often been used for tuning the large‐scale performance of operational numerical weather prediction (NWP) models, although it is widely recognized to be detrimental for an accurate representation of stable boundary layers. Here we investigate why, 20 years on, such a compromise is still needed in the ECMWF model. We find that reduced turbulent diffusion in stable conditions improves the representation of winds in stable boundary layers, but it deteriorates the large‐scale flow and the near‐surface temperatures. This suggests that enhanced diffusion is still needed to compensate for errors caused by other poorly represented processes. Among these, we identify the orographic drag, which influences the large‐scale flow in a similar way to the turbulence closure for stable conditions, and the strength of the land‐atmosphere coupling, which partially controls the near‐surface temperatures. We also take a closer look at the relationship between the turbulence closure in stable conditions and the large‐scale flow, which was not investigated in detail with a global NWP model. We demonstrate that the turbulent diffusion in stable conditions affects the large‐scale flow by modulating not only the strength of synoptic cyclones and anticyclones, but also the amplitude of the planetary‐scale standing waves. Key Points: some NWP models use excessive diffusion in stable conditions reducing turbulent diffusion improves stable boundary layers enhanced diffusion helps offsetting errors due to other processes